Effects of a foot-ankle strengthening programme on clinical aspects and gait biomechanics in people with knee osteoarthritis: protocol for a randomised controlled trial - Tania F Salvini; Glauko Dantas; Isabel C N Sacco; Ana F dos Santos; Ricky Watari; Alessandra B Matias; Paula R M S Serrao; Henrique Pott-Junior (BMJ Open)
Introduction Studies have indicated that hip and knee muscle strengthening are effective in reducing pain, improving self-reported function and increasing lower limb strength, without, however, decreasing knee joint overload during gait in patients with knee osteoarthritis (KOA). Recent research has shown that strengthening the foot-ankle muscles improved function in diabetic patients and reduced patellofemoral pain. The aim of this paper is to investigate whether an 8-week therapeutic foot-ankle exercise programme improves pain, functionality, foot strength, foot kinematics and knee joint overload during gait, and decreases medication intake in individuals with KOA.Methods and analysis This two-arm, prospectively registered, randomised controlled trial with blinded assessors will involve 88 patients with medial tibiofemoral osteoarthritis. Subjects will be randomly allocated to a control group that will receive no specific foot intervention and will follow treatment recommended by the medical team; or an intervention group that will undergo an 8-week physiotherapist-supervised strengthening programme for extrinsic and intrinsic foot muscles, three times a week. The primary outcome will be the pain domain of the Western Ontario McMaster Universities Osteoarthritis Index (WOMAC). The secondary outcomes include WOMAC stiffness and function domains, total WOMAC score, physical function, foot muscle isometric strength, foot kinematics and knee kinetics during gait, and medication intake. Data will be analysed on intention-to-treat principles and a per protocol basis.Ethics and dissemination Investigators and sponsors will communicate trial results to participants and healthcare professionals through scientific databases and social media. In addition, findings will be reported in peer-review publications, and at national and international conference presentations. Ethics approval: Ethics Committee of the Universidade Federal de São Carlos, São Carlos, SP, Brazil (N° 3.488.466).Trial registration number NCT04154059.